A Correlation between Students' Intensity of Watching English videos on YouTube and Their Listening Achievement in the 3rd Semester English Education Department of UIN Sultan Syarif Kasim Riau - Dersa, Sovie Lindaita; Hasibuan, Kalayo (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This research aimed to see is there any significant correlation between students’ intensity of watching English videos on YouTube and their listening achievement at the 3rd semester of English Education Department UIN Sultan Syarif Kasim Riau. This research used quantitative research. This research used correlational research design. This research was held on October 5th – 30th, 2022 at UIN Sultan Syarif Kasim Riau. The research data was collected from 34 samples and were selected by technique simple random sampling. The sample of this research was the third semester students of English Education Department UIN Sultan Syarif Kasim Riau. To gather the data, this research used questionnaire and documentation. This research used pearson product moment and simple linear regression to analyse the data. The findings of this research showed that the students’ intensity of watching English videos on YouTube had no contribution on students’ listening achievement. It means that there is no significant correlation between students’ intensity of watching English videos on YouTube on students’ listening achievement at the third semester students of English Education Department UIN Sultan Syarif Kasim Riau.